1984
DOI: 10.1007/bf00281117
|View full text |Cite
|
Sign up to set email alerts
|

Separate influence of dietary carbohydrate and fibre on the metabolic control in diabetes

Abstract: To clarify the separate influences of digestible carbohydrate and of dietary fibre on blood glucose control and serum lipoproteins, 14 diabetic patients (six Type 1 and eight Type 2) were submitted to three weight-maintaining diets for 10 days each: (1) low carbohydrate/low fibre diet with 42% carbohydrate and 20 g fibre; (2) high carbohydrate/low fibre diet (carbohydrate 53%, fibre 16 g); (3) high carbohydrate/ high fibre diet (carbohydrate 53%, fibre 54 g). In comparison with the low carbohydrate/low fibre d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
37
0
1

Year Published

1990
1990
2009
2009

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(42 citation statements)
references
References 19 publications
4
37
0
1
Order By: Relevance
“…We were also able to show that it was possible to achieve beneficial effects with more acceptable amounts of dietary fibre than had been used in our earlier studies (Lousley et al, 1984). Other groups publishing at around the same time or shortly afterwards produced broadly comparable results (Rivellese et al, 1980;Riccardi et al, 1984). Those who were unable to duplicate these findings may have used foods which were not sufficiently rich in soluble fibre (Hollenbeck et al, 1988).…”
supporting
confidence: 51%
“…We were also able to show that it was possible to achieve beneficial effects with more acceptable amounts of dietary fibre than had been used in our earlier studies (Lousley et al, 1984). Other groups publishing at around the same time or shortly afterwards produced broadly comparable results (Rivellese et al, 1980;Riccardi et al, 1984). Those who were unable to duplicate these findings may have used foods which were not sufficiently rich in soluble fibre (Hollenbeck et al, 1988).…”
supporting
confidence: 51%
“…Daily consumption of a diet containing 20-35g dietary fiber from a wide variety of food sources is recommended (14). Several previous studies using dietary fiber levels of 45-50g/d showed little or no significant benefits to carbohydrate metabolism in patients with diabetes (16)(17)(18), and the greatest effects on carbohydrate metabolism have relied on dietary fiber levels from 70 to 100g/d (19)(20)(21), but these levels of dietary fiber intake may be impossible to achieve consistently in a large segment of the population (15). On the other hand, most of the previous studies on dietary fiber in diabetic patients or diabetic animals used single-type dietary fiber such as water-soluble dietary fiber or water-insoluble dietary fiber as a food admixture.…”
Section: Discussionmentioning
confidence: 99%
“…Of these reports, 226 were excluded based on other criteria, leaving 41 trials (39 reports) that satisfied the inclusion criteria but did not meet the exclusion criteria, of which 11 trials (ten reports) investigated pulses alone, 19 trials (19 reports) investigated pulses in a low-GI dietary intervention, and 11 trials (ten reports) investigated pulses in a high-fibre dietary intervention. Tables 1, 2, and 3 show the characteristics of the 41 randomised controlled experimental trials included in each of the three meta-analyses: pulses alone [45][46][47][48][49][50][51][52][53][54], pulses in low-GI diets [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] and pulses in highfibre diets [55][56][57][58][59][60][61][62][63][64]. The 11 trials (ten reports) investigating pulses alone (Table 1) were predominantly crossover in design (seven trials, five of which had a washout period), studied a total of 253 participants (type 2 diabetes, n=21; normoglycaemia and/or hypercholesterolaemia, n=232) and had a mean sample size of 23.…”
Section: Methodsmentioning
confidence: 99%